2020
DOI: 10.1111/pedi.13160
|View full text |Cite
|
Sign up to set email alerts
|

Performance of three different continuous glucose monitoring systems in children with type 1 diabetes during a diabetes summer camp

Abstract: The aim of this study was to assess accuracy of the three most commonly used continuous glucose monitoring (CGM) systems in almost real‐life situation during a diabetes camp in children with type 1 diabetes (T1D) aged 9–14 years. Data was gathered during a 2‐week summer camp under physicians' supervision. Out of 38 participating children with T1D (aged: 11.0 [9.9; 12.1] years; 57% girls, mean HbA1c 7.2 [6.9; 7.7] %,) 37 wore a CGM system (either Abbott FreeStyle Libre (FSL), Dexcom G6 (DEX) or Medtronic Enlite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…27 Thus, it is likely that the CGMS would perform within hypoglycemic ranges in foals (reportable glucose range of the device is 40-400 mg/dL), but this supposition will need to be confirmed in future studies of foals because another study in children observed better performance of the Dexcom G6 in the normoglycemic range compared to hypoglycemic measurements. 30 In summary, the CGMS provided accurate and immediate glucose concentration results within the glucose concentrations observed in our study. Further evaluation is necessary in hypoglycemic neonatal foals, but the CGMS might serve as a method of evaluating glucose concentration in hospitalized ill foals while eliminating the need for repeated blood collection from patients.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…27 Thus, it is likely that the CGMS would perform within hypoglycemic ranges in foals (reportable glucose range of the device is 40-400 mg/dL), but this supposition will need to be confirmed in future studies of foals because another study in children observed better performance of the Dexcom G6 in the normoglycemic range compared to hypoglycemic measurements. 30 In summary, the CGMS provided accurate and immediate glucose concentration results within the glucose concentrations observed in our study. Further evaluation is necessary in hypoglycemic neonatal foals, but the CGMS might serve as a method of evaluating glucose concentration in hospitalized ill foals while eliminating the need for repeated blood collection from patients.…”
Section: Discussionsupporting
confidence: 77%
“… 27 Thus, it is likely that the CGMS would perform within hypoglycemic ranges in foals (reportable glucose range of the device is 40‐400 mg/dL), but this supposition will need to be confirmed in future studies of foals because another study in children observed better performance of the Dexcom G6 in the normoglycemic range compared to hypoglycemic measurements. 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, using two different brands of sensor between the experimental and control phases, with different accuracy, could have introduced a bias to the outcomes. 15 Overall, our extension study provides a strong argument for proposing the use of DBLHU in all T1D patients with severe clinical and metabolic features indicating an islet or pancreas transplantation.…”
Section: Satisfactionmentioning
confidence: 67%
“…So the difference in the sensor used may have been related. Howard R et al reported that FLP-CGM tended to produce lower mean blood glucose levels than Dexcom G4 Platinum 18 , and Nagl K et al reported that FLP-CGM had a greater mean absolute relative difference (MARD) and lower mean glucose levels than Dexcom G6 and Medtronic Enlite19 . Third, the subjects of this study were Japanese patients with T2DM, and racial differences may also be relevant.…”
mentioning
confidence: 99%